(untitled) (Revista de Crítica Literaria Latinoamericana, 2017)
This short article is about Las Posadas, and the direct and less known link of Inca Garcilaso to the Las Posadas’ chancellor and old friend, Gonzalo Silvestre. The article also focuses on how Silvestre’s quest for recognition and nobility, his eagerness to get merits from the Crown, caught in the Inca the need to reassert himself as a noble mestizo, to clear the name of his father and to project the sacrifice of the Spaniards in their conquests in Peru and in La Florida. Although Silvestre has been identified and recognized as the main informant of La Florida del Inca, our historical essay reveals the influence of the old Spanish captain over the later, most famous works of Inca Garcilaso de la Vega.